The clamour for an end to police brutality: satire songs of the endsars protests in Nigeria (2021)
The EndSars protests, which occurred in Nigeria in October 2020 employed a great deal of music, which include solidarity songs, popular music, and satirical songs. This article investigates the use of satirical songs in the EndSars protests. The protest, which recorded a massive turnout of protesters in October 2020 across major cities in Nigeria started several months on the social media, most especially Twitter, a microblogging website before it was finally taken to the streets. Anchored on the concept of social movement, it employs the use of participant observation and the social media platforms to gather data which were analysed using content analysis. Apart from being used to ridicule the Nigerian Police which has not engaged Boko-Haram terrorists but instead unleashes terror on harmless youths, satirical songs were used by protesters to express their long piled up anger at the Federal Government of Nigeria. This is due to several unfulfilled campaign promises, as well as the bad state of the nation’s economy which has contributed to the hike in price of food items and other essential commodities, coupled with the growing rate of unemployment. The Nigerian government should use the opportunity created by the massive protests to execute a thorough reform of the Nigerian security establishments and also engage youths more productively in order to enable them to contribute their quota to nation-building.